The Expediency of Using the Results of Psyhophysiological Research Conduction Using a Computer Polygraph in the Collection of Evidence in Criminal Proceedings Against the Life and Health of a Person - Цехан, Дмитро Миколайович; Цехан, Д. М.; Tsekhan, Dmytro M.; Мурашко, Анастасия Сергеевна; Murashko, Anastasyia S.; Мурашко, А. С. (Centre for European Reforms Studies, a.s.b.l. Grand Duchy of Luxembourg, 2021)
the article analyzes the feasibility of using the results of psychophysiological research carried out using a computer polygraph in the collecting evidence in criminal proceedings against human life and health. Attention is drawn to the state of the current legislation, which allows the use of a polygraph on the territory of Ukraine. Cases are highlighted in which the investigator should apply for a psychophysiological study using a computer polygraph during the investigation of crimes against human life and health: conducting a psychophysiological study using a computer polygraph, when, during the repeated interrogation of a suspect/witness, there are conflicting testimonies or a change in testimony the person being interrogated; the use of psychophysiological research using a computer polygraph in the investigation of crimes against the life and health of a person of past years; when the suspect/accused insists on conducting a psychophysiological study using a computer polygraph. It is indicated that conducting the designated research has a tactical function during the investigation of crimes. It is also proposed to supplement Part 3 of Art. 42 of the Criminal Procedure Code of Ukraine, clause 12-1 of the following content: "Submit a petition to conduct a psychophysiological research using a computer polygrap.

В статье проанализирована целесообразность использования результатов психофизиологического исследования, проведённого с помощью компьютерного полиграфа, при сборе доказательств по уголовным производствам против жизни и здоровья человека. Обращено внимание на состояние действующего законодательства, которое позволяет использование полиграфа на территории Украины. Выделены случаи, при которых следователю следует обращаться за проведением психофизиологического исследования с помощью компьютерного полиграфа во время расследования преступлений против жизни и здоровья человека: проведение психофизиологического исследования с использованием компьютерного полиграфа, когда при повторном допросе подозреваемого/свидетеля имеют место противоречивые друг другу показания или изменение показаний допрашиваемого; использование психофизиологического исследования с помощью компьютерного полиграфа при расследовании преступлений против жизни и здоровья человека прошлых лет; когда подозреваемый/обвиняемый выступает инициатором проведения психофизиологического исследования с помощью компьютерного полиграфа. Указано, что проведение обозначенного исследования имеет тактическую функцию во время расследования преступлений. Так же предложено дополнить ч. 3 ст. 42 Криминального процессуального кодекса Украины пунктом 12-1 такого содержания: «Заявлять ходатайство о проведении психофизиологического исследования с использованием компьютерного полиграфа».

У статті проаналізовано доцільність використання результатів психофізіологічного дослідження, проведеного за допомогою комп'ютерного поліграфа, під час збору доказів з кримінальних проваджень проти життя та здоров'я людини. Звернено увагу на стан чинного законодавства, що дозволяє використання поліграфу на території України. Виділено випадки, за яких слідчому слід звертатися за проведенням психофізіологічного дослідження за допомогою комп'ютерного поліграфа під час розслідування злочинів проти життя та здоров'я людини: проведення психофізіологічного дослідження з використанням комп'ютерного поліграфа, коли при повторному допиті підозрюваного/свідка мають місце суперечливі один одному показання або зміна показань допитуваного; використання психофізіологічного дослідження за допомогою комп'ютерного поліграфа при розслідування злочинів проти життя та здоров'я людини минулих років; коли підозрюваний/обвинувачений виступає ініціатором проведення психофізіологічного дослідження за допомогою комп'ютерного поліграфу. Вказано, що проведення зазначеного дослідження має тактичну функцію під час розслідування злочинів Також запропоновано доповнити ч. 3 ст. 42 Кримінального процесуального кодексу України пунктом 12-1 такого змісту: «Заявляти клопотання про проведення психофізіологічного дослідження з використанням комп'ютерного поліграфа».
Tsekhan D. M. The Expediency of Using the Results of Psyhophysiological Research Conduction Using a Computer Polygraph in the Collection of Evidence in Criminal Proceedings Against the Life and Health of a Person / D. M. Tsekhan, A. S. Murashko // European Reforms Bulletinscientific: scientific peer-reviewed journal. – No. 1. – Centre for European Reforms Studies, a.s.b.l. Grand Duchy of Luxembourg, 2021. – P. 92-96.
Keywords: psychophysiological research; polygraph; evidence; investigator; crimes against life and health; психофизиологическое исследование; полиграф; доказательство; следователь; преступления против жизни и здоровья; психофізіологічне дослідження; поліграф; доведення; слідчий; злочини проти життя та здоров'я; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Research Subject Categories::TECHNOLOGY